A place to stand: Proverbs 8 and the construction of ecclesial space. Issue 2 (19th April 2017) - Collett, Donald
Abstract: Recent debate over the question whether 'amôn in Proverbs 8:30 should be rendered in a passive or active sense is helpful for illuminating the nature of the interaction between theology and exegesis in biblical interpretation. This essay offers an assessment of this debate with a view towards clarifying its christological significance, arguing that the semantics and syntax of Proverbs 8:30, as well as the theological frame of reference established by verses 22–31, exert an 'ontological pressure' upon our understanding of divine identity in Proverbs 8. These considerations offer an alternative avenue of approach to the poem that honours the Old Testament's commitment to monotheism, while also allowing the Old Testament's own presentation to shape our understanding of the character of theLord 's oneness.